Newborn Care Practices and Associated Factors Influencing Their Health in a Northern Rural India - Md Arfin Islam; Md Suhail Khan; Anas Ahmad Khan; Bayapa Reddy Narapureddy; Kalyan Viswanath Reddy Lingala; Nazim Nasir; Khursheed Muzammil; Irfan Ahmad; Adam Dawria; Ahmed Faheem; Ali Mohieldin (MDPI AG, 2023)
Introduction: In developing countries, neonatal mortality is the most neglected health issue by the health system, leading to its emergence as a public health problem. A study was undertaken to assess the influence of factors and newborn care practices influencing newborn health in the rural area of Bareilly district. Methodology: The descriptive cross-sectional study was organized in the rural areas of Bareilly. Study participants were selected based on the mothers who gave birth to a baby during the last six months. The mothers who delivered in that area within six months were included and, using the semi-structured questionnaire, data were collected. Data were analyzed using Microsoft Excel and SPSS 2021 version for windows. Results: Out of 300 deliveries, nearly one-quarter of the deliveries, 66 (22%), were happening in homes, and most of the deliveries, 234 (78%), happened in hospitals. It was observed that unsafe cord care practices were observed more among nuclear families, 8 (53.4%), than joint families, 7 (46.6%), and it was found to be statistically insignificant. The Unsafe feed was given 48 (72.7%) more commonly among home deliveries than institutional deliveries 56 (23.9%). Mothers' initiation of delayed breastfeeding was nearly the same in both home and hospital deliveries. Delayed bathing was observed in nearly three-fourths of mothers, 125 (70.1%), aged 24-29 years, followed by 29 (16.8%) in the age period of 30-35 years. Conclusion: The practice of essential newborn care still needs to improve in Bareilly; there is a need to create awareness among the mothers and family members on newborn and early neonatal care aspects, such as promoting exclusive and early initiation of breastfeeding and delayed bathing practices.